Electrochemical behavior of gold colloidal alkyl modified silicon surfaces - Le Saux, G.; Ciampi, Simone; Gaus, K.; Gooding, J. (American Chemical Society, 2009)
Herein, we report on the production of nanoelectrode arrays by attaching colloidal gold on silicon-bound mixed self-assembled monolayers of TFA-protected alkenylthiol (C 11-S-TFA) and undecylenic acid (acid). Effective modification of the surface, tethering of the nanoparticles, and the direct influence of the deprotected alkenylthiol (C 11-SH) /acid ratio on the number of adherent particles were demonstrated using X-ray photoelectron spectroscopy, electrochemistry, and atomic force microscopy. Cyclic voltammetry showed that the enhancement of electron transfer to the silicon surface by the presence of nanoparticles is influenced by the number of tethered nanoparticles. © 2009 American Chemical Society.